Environment-independent liquid level sensing based on fiber-optic displacement sensors - Yang, Hang Zhou; Harun, Sulaiman Wadi; Arof, Hamzah; Ahmad, Harith (John Wiley & Sons, 2011)
A new fiber-optic liquid-level sensor (LLS) for continuous monitoring of the liquid level is proposed using a fiber-optic displacement sensor (FODS). A float is used to measure the level of liquid in the tank and it is connected to the FODS probe to convert the variation of the liquid level into a displacement change. The performance of the LLS is investigated for two different FODSs with a concave and a flat mirror target. With a concave mirror, six measurement slopes within a range of 25 mm are observed with the highest sensitivity of 1.3015 mV/mm. With a flat mirror, two measurement slopes are observed with the highest sensitivity of 1.4533 mV/mm and the longest measurement range of 4.8 mm.